Can company size moderate corporate social responsibility disclosure effect on company profitability? Evidence from mining industry - Rahmawati Rahmawati; Riyanti Riyanti; Marwah Yusuf (Faculty of Islamic Economics and Business of Universitas Islam Negeri Mataram, 2024)
Purpose — This study aims to examine the moderating effect of the company size on the relationship between Corporate Social Responsibility (CSR) disclosure and company profitability in mining industry.Method — This study employs multiple regression to examine the relationship between CSR disclosure and profitability using ROA and ROE proxies, with company size as a moderator. The observations were conducted on 12 mining companies listed on the Indonesia Stock Exchange during the period of 2018-2022.Result — We found that company size moderates the relationship between CSR disclosure and company profitability, using ROA and ROE as proxies. The results indicate that CSR disclosure had a positive and significant effect on company profitability when measured with ROA proxies but did not show significance with ROE proxies.Contribution — This research contributes by using company size variable as the moderator in the relationship between CSR disclosure and financial performance.